2017
DOI: 10.1038/s41467-017-00748-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Up states induce the selective weakening of subthreshold synaptic inputs

Abstract: Slow-wave sleep is thought to be important for retuning cortical synapses, but the cellular mechanisms remain unresolved. During slow-wave activity, cortical neurons display synchronized transitions between depolarized Up states and hyperpolarized Down states. Here, using recordings from LIII pyramidal neurons from acute slices of mouse medial entorhinal cortex, we find that subthreshold inputs arriving during the Up state undergo synaptic weakening. This does not reflect a process of global synaptic downscali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 71 publications
0
36
0
Order By: Relevance
“…Finally, another recent study identified a potential candidate to tag the synapses that need to be protected from down‐selection, the opposite of what Arc would do. The experiments were performed in acute slices of adolescent mouse medial entorhinal cortex, which maintain UP/DOWN states like those seen during NREM sleep (Bartram et al., ). Using whole‐cell recordings from pyramidal neurons of layer 3, it was found that inputs arriving during the UP states underwent synaptic weakening unless they were paired with postsynaptic spiking.…”
Section: Molecular Candidates For Sleep‐dependent Synaptic Down‐selecmentioning
confidence: 99%
“…Finally, another recent study identified a potential candidate to tag the synapses that need to be protected from down‐selection, the opposite of what Arc would do. The experiments were performed in acute slices of adolescent mouse medial entorhinal cortex, which maintain UP/DOWN states like those seen during NREM sleep (Bartram et al., ). Using whole‐cell recordings from pyramidal neurons of layer 3, it was found that inputs arriving during the UP states underwent synaptic weakening unless they were paired with postsynaptic spiking.…”
Section: Molecular Candidates For Sleep‐dependent Synaptic Down‐selecmentioning
confidence: 99%
“…Neuronal UP states are known to play an important role in the consolidation of memory (Marshall, Helgadottir, Molle, & Born, ), but the exact cellular mechanism by which UP states control storage of information in the brain is poorly understood. A recent study showed that UP state‐induced synaptic weakening of subthreshold inputs, while preserving synaptic strength of strong inputs (Bartram et al, ). This cellular mechanism causes a near‐global synaptic downscaling during slow wave sleep.…”
Section: Part 2: Single Neuron Significancementioning
confidence: 99%
“…It was recently shown that sleep yields a net decrease in the firing rates of both hippocampal (Miyawaki and Diba, 2016) and frontal cortex neurons (Watson et al, 2016). These changes were likely explained by synaptic downscaling (Tononi and Cirelli, 2014), triggered in the hippocampus by sharp-wave ripples and sleep spindles during NREM sleep, and incorporated over the course of REM sleep (Miyawaki and Diba, 2016) and in the neocortex, triggered by alternating cycles of UP/DOWN states (Bartram et al, 2017;Gulati et al, 2017). In Miyawaki and Diba (2016) and Watson et al (2016) , we took trouble to evaluate firing rate changes between different epochs of the same state (e.g.…”
Section: Introductionmentioning
confidence: 99%